Chain Substituted Cannabilactones with Selectivity for the CB2 Cannabinoid Receptor - Shakiru O. Alapafuja; Spyros P. Nikas; Thanh C. Ho; Fei Tong; Othman Benchama; Alexandros Makriyannis (Molecules, 2019)
In earlier work, we reported a novel class of CB2 selective ligands namely cannabilactones. These compounds carry a dimethylheptyl substituent at C3, which is typical for synthetic cannabinoids. In the current study with the focus on the pharmacophoric side chain at C3 we explored the effect of replacing the C1′-gem-dimethyl group with the bulkier cyclopentyl ring, and, we also probed the chain’s length and terminal carbon substitution with bromo or cyano groups. One of the analogs synthesized namely 6-[1-(1,9-dihydroxy-6-oxo-6H-benzo[c]chromen-3-yl) cyclopentyl] hexanenitrile (AM4346) has very high affinity (Ki = 4.9 nM) for the mouse CB2 receptor (mCB2) and 131-fold selectivity for that target over the rat CB1 (rCB1). The species difference in the affinities of AM4346 between the mouse (m) and the human (h) CB2 receptors is reduced when compared to our first-generation cannabilactones. In the cyclase assay, our lead compound was found to be a highly potent and efficacious hCB2 receptor agonist (EC50 = 3.7 ± 1.5 nM, E(max) = 89%). We have also extended our structure-activity relationship (SAR) studies to include biphenyl synthetic intermediates that mimic the structure of the phytocannabinoid cannabinodiol.